Overview of a Computer-based Stuttering Therapy - Ooi, Chia Ai; Yunus, Jasmy (School of Postgraduate Studies, UTM, 2006)
The purpose of this paper is to introduce the reader to a variety of anti-stuttering devices that have been used to treat stuttering. The use of devices to cure, or at least control, stuttering is not new. A variety of devices have been utilized, with a variety of purposes. A few examples of each of the different classes of devices are discussed. Reviews on these various electronic devices are presented where there is no one best treatment for stuttering for every client. It is suggested that choosing different types of stuttering managements is a personal decision based on the unique values and treatment objectives of each individual person who stutters. This leads to the implementation of our computer-based Malay stuttering therapy to help Speech-Language Pathologist (SLP) to determine suitable technique for each client. The project implements Digital Signal Processing (DSP) techniques to analyze speech signals and incorporates fluency shaping techniques. Our hypothesis is by doing comparison between clientÂ’s and clinicianÂ’s Average Magnitude Profiles (AMPs)for different techniques, the computer analysis can help SLP to determine suitable techniques in faster and more accurate manner. This will reduce cost and time for therapy. We believe our software tool will improve the effectiveness and availability of stuttering therapy in Malaysia.We hope that our software tool will provide insights into the implementation of computer-based Malay stuttering therapy in Malaysia.